ANALISA ALAT ROTARY KILN DI PABRIK 2 PT. SEMEN BATURAJA Tbk. DITINJAU DARI EFFISIENSI THERMAL DAN EMISI GAS BUANG - Syafitri, Neza; Safaruddin, Safaruddin; Muzzak, Mukti Mabrur (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study focuses on evaluating the thermal efficiency and exhaust emissions produced by the rotary kiln used in Factory 2 PT. Semen Baturaja Tbk. As a central component in the cement production process, rotary kiln performance has a significant impact on factory operations and the surrounding environment. This study combines direct measurement of exhaust emissions with analysis of kiln operational data to identify achieved levels of thermal efficiency and the impact of exhaust gases on the environment. The results of this study are expected to provide an in-depth view of the rotary kiln performance in terms of thermal efficiency and exhaust emissions. By understanding the factors that affect efficiency and emissions, manufacturers can design appropriate remedial measures to increase thermal efficiency and reduce environmental impact. The positive results of this research can contribute to sustainable practices in the cement industry, by ensuring that the production process is not only energy efficient but also environmentally friendly